What Do News Disseminators and Audiences in the Digital Age Need Most? — Skills? Knowledge? Or Accuracy-Motivated Sceptical Knowing - Chang (常力轩), Lixuan; Nie (聂静虹), Jinghong (Javnost-The Public, 2024)
In the digital age, journalism encounters both challenges and opportunities. Drawing on a wide range of classic discussions and investigative experiments, this article introduces the concept of “accuracy-motivated sceptical knowing.” This concept, driven by the verification of factual accuracy, represents a professional form of sceptical knowing and is crucial for becoming a responsible media professional and an informed citizen. This article discusses the necessity of transitioning from “general scepticism” to accuracy-motivated sceptical knowing. From the perspectives of both the disseminator and the audience, this article proposes methods for accuracy-motivated sceptical knowing: the disseminator should persist and innovate, while the audience should focus on the source, evidence, openness, and education, and both disseminators and audiences should embrace the “Hurtt Six Points” — questioning, suspension, search, empathy, self-esteem, and autonomy. Finally, this article clarifies the difference between accuracy-motivated sceptical knowing and related concepts, as well as the boundaries of its application.